Developmental changes of central conduction time of evoked potentials in infants and children - Tien, Y; Yasuhara, A; Araki, A; Kobayashi, Y (No to hattatsu, 1994)
We investigated the developmental changes of the central conduction time (CCT) of the median nerve somatosensory evoked potential (SEP) and the auditory evoked potential (ABR): SEP was recorded in 148 children and adults, and ABR in 307 subjects. We determined the rostral CCT (CCT 1:P 14 to N 17) and the caudal CCT (CCT 2:N 17 to N 19), because the central sensory tract was long, and included the spinal tract, brainstem, thalamus and cerebral cortex. The greatest changes in CCT of SEP occurred during early infancy (0 to 6 months of age). The latency of SEP gradually decreased with maturation. CCT 2 showed similar developmental patterns and was longer than CCT 1 during 0 to 4 months of age. Developmental changes in CCT 1 linearly decreased as age increased. The CCT of ABR also decreased as age increased. The maturation of I-III interpeak latency (IPL) (2 years of age) was earlier than the III-V IPL (3 years of age). The maturation of both ABR and SEP was seen from the rostral to caudal direction. The correlation coefficients of CCT, CCT 1 and CCT 2 divided by body height were 0.86, 0.77 and 0.69, respectively. They were higher than non-divided correlation coefficients. CCTs of the short latency SEPs were also related to body height.